Content analysis of targeted food and beverage advertisements in a Chinese-American neighbourhood - Bragg, Marie A.; Pageot, Yrvane K.; Hernández Villarreal, María Olivia; Kaplan, Sue A.; Kwon, Simona C. (behalf of the Nutrition Society by CAB International, 2017)
Abstract Objectives: The current descriptive study aimed to: (i) quantify the number and type of advertisements (ads) located in a Chinese-American neighbourhood in a large, urban city; and (ii) catalogue the targeted marketing themes used in the food/beverage ads. Design: Ten pairs of trained research assistants photographed all outdoor ads in a 0·6 mile2 (1·6km2) area where more than 60·0% of residents identify as Chinese American. We used content analysis to assess the marketing themes of ads, including references to: Asian cultures; health; various languages; children; food or beverage type (e.g. sugar-sweetened soda). Setting: Lower East Side, a neighbourhood located in the borough of Manhattan in New York City, USA. Subjects: Ads (n 1366) in the designated neighbourhood. Results: Food/beverage ads were the largest ad category (29·7%,n 407), followed by services (e.g. mobile phone services; 21·0%, n 288). Sixty-seven per cent (66·9%) of beverages featured were sugar-sweetened, and 50·8% of food ads promoted fast food. Fifty-ﬁve per cent (54·9%) of food/beverage ads targeted Asian Americans through language, ethnicity of person(s) in the ad or inclusion of culturally relevant images. Fifty per cent (50·2%) of ads were associated with local/small brands. Conclusions: Food/beverage marketing practices are known to promote unhealthy food and beverage products. Research shows that increased exposure leads to excessive short-term consumption among consumers and inﬂuences children’s food preferences and purchase requests. Given the frequency of racially targeted ads for unhealthy products in the current study and increasing rates of obesity-related diseases among Asian Americans, research and policies should address the implications of food and beverage ads on health